Fossil birds from Cooper's D aid in reconstructing the Early Pleistocene paleoenvironment in the Cradle of Humankind (Gauteng, South Africa). Issue 167 (June 2022) - Pavia, Marco; Val, Aurore; Carrera, Lisa; Steininger, Christine M.
Abstract: Several large-bodied hominin and nonhuman primates have coexisted in the Cradle of Humankind in South Africa during the Early Pleistocene. Previous paleoenvironmental studies regarding the Plio-Pleistocene of South Africa have focused heavily on mammal assemblages. Here, we conducted a comprehensive taxonomic analysis of the fossil bird remains from Cooper's D, the most fossiliferous locality of the hominin-bearing Cooper's Cave complex in South Africa. Our taxonomic evaluation of 505 remains reveals the presence of 23 bird taxa, two of which are extinct and already reported from the nearby fossil locality of Kromdraai. The taxonomically diverse bird assemblage is dominated by Francolinus sp. and other species associated with open grassland habitats, followed by rock-dwelling species, including Tyto cf. alba and the extinct Corvus bragai, and by woodland species such as Agapornis sp., Accipiter melanoleucos, and the extinct Glaucidium ireneae . The occurrence of these taxa and their respective proportions in the assemblage, in terms of both numbers of bones and individuals, point to the presence of extensive open grassland and/or savannah with rocky outcrops and woodland. These findings corroborate previous analyses of mammals from Cooper's D, with the exception of aquatic species, which are rare in the bird assemblage. Comparison with older deposits from Kromdraai confirms the definitive establishment of open habitats in the Cradle of Humankind during the Early Pleistocene following a transition from woodier habitats during the Late Pliocene. This study constitutes a further step in investigating the fossil bird diversity in the Cradle of Humankind during the Plio-Pleistocene. Our results add to the larger body of work using avian fossils for paleoenvironmental reconstructions in Africa and support the utility of birds as paleoenvironmental proxies. Similar future studies will refine our understanding of the paleoenvironments and landscape transformation during the Plio-Pleistocene, a critical timeframe for hominin evolution in southern Africa.